Extranodal localization of non-Hodgkin's lymphoma in systemic sclerosis: A diagnostic challenge and review of the literature. Issue 3 (October 2022) - Galoppini, Giorgio; Maranini, Beatrice; Ciancio, Giovanni; Padovan, Melissa; Casoni, Gian Luca; Cavazzini, Francesco; Gafà, Roberta; Lanza, Giovanni; Govoni, Marcello
Background: Systemic sclerosis is associated with an increased incidence of malignancies, in particular solid neoplasms. Hematological cancers have been also observed in autoimmune diseases, though rarely present with lung involvement. The latter may be misdiagnosed in systemic sclerosis patients, due to the frequent concomitant interstitial lung disease. Case description: Here, we present the case of a 63-year-old man affected by systemic sclerosis presenting with an atypical lung imaging and splenomegaly, who was diagnosed with splenic marginal zone lymphoma, thus raising the suspicion of lung secondarism. We discuss the diagnostic challenge of differential diagnosis in interstitial lung presentation and briefly review the available literature on this topic. Conclusion: Several reports have demonstrated an increased risk of malignancy in patients with systemic sclerosis. Still, the lack of concretely defined guidelines for systemic sclerosis, along with systemic sclerosis multifaceted organ involvement at presentation, may challenge diagnosis and management. Here, we remark the importance of clinical work-up and a multidisciplinary approach in systemic sclerosis, to early detect and treat concomitant hematological malignancies, especially during the first years of the disease.